2015
DOI: 10.12659/msm.893881
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extra Virgin Olive Oil on Biomarkers of Inflammation in HIV-Infected Patients: A Randomized, Crossover, Controlled Clinical Trial

Abstract: BackgroundPremature atherosclerosis in HIV-infected patients is associated with chronic infection by itself and adverse effects of antiretroviral treatment (ART). Extra virgin olive oil (EVOO) has a beneficial effect on the cardiovascular system because of its anti-inflammatory properties.The objective of this study was to determine whether the consumption of EVOO improves inflammation and atherosclerosis biomarkers in HIV-infected patients receiving ART.Material/MethodsThis randomized, crossover, controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…[18] Experience in HIV-infected patients is limited, although there has also been evidence of a decrease in CRP levels in patients who used older ART regimens that are no longer in use. [26]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] Experience in HIV-infected patients is limited, although there has also been evidence of a decrease in CRP levels in patients who used older ART regimens that are no longer in use. [26]…”
Section: Discussionmentioning
confidence: 99%
“…The published experience on the effects of the use of EVOO in patients with HIV infection is very scarce, [26] suggesting a positive effect on inflammatory markers such as ultrasensitive C-reactive protein (CRP), so we aimed to observe the effects of daily EVOO intake in a group of patients with chronic HIV infection and long-term ART use, analyzing its effects on the lipid profile, inflammatory parameters, and intestinal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with our results, a study similar to ours that investigated the effects of the consumption of EVOO in comparison to ROO in HIV-infected patients reported no significant differences in several cardiovascular risk markers (IL-6, fibrinogen, total cholesterol, HDL-cholesterol, triglycerides, ESR) after EVOO intake. Additionally, they did not find any difference after ROO consumption, except for a lower LDL-cholesterol level [30].…”
Section: Discussionmentioning
confidence: 80%
“…Several authors did not find significant changes in ESR after consumption of EVOO in comparison to ROO in HIV-infected patients. However, the same authors found that the EVOO intervention reduced ESR compared to baseline values in a subgroup of HIV-infected patients receiving antiretroviral treatment [30]. Although we failed to find significant improvements on other inflammatory parameters such as CRP or IL-6 after 3-week olive oil consumption in women with FM, results of the PREDIMED study showed that 3-month consumption of a Mediterranean diet supplemented with virgin olive oil reduced CRP and IL-6 levels in subjects at high risk for cardiovascular disease when compared with a low-fat diet [31,32].…”
Section: Discussionmentioning
confidence: 94%
“…Twenty RTCs examined the effect of EVOO on LDL-c [33,40,[45][46][47][48]50,[55][56][57][58][59][60][61][62][63][64][65][66][67][68]. Of these, nine included the total phenol content of the EVOO studied [33,41,42,50,53,54,61,62,68].…”
Section: Low-density Lipoprotein Cholesterol (Ldl-c)mentioning
confidence: 99%